Forest genetic resources conservation and management: Proceedings of the Asia Pacific Forest Genetic Resources Programme (APFORGEN) Inception Workshop, Kepong, Kuala Lumpur,Malaysia, 15-18 July 2003 - Luoma-aho, T.; Hong, L.T.; Ramanatha Rao, V.; Sim, H.C.; International Plant Genetic Resources Institute (2004)
Conservation, improvement, and effective management of forest genetic resources (FGR) is basic to sustainable forest management but will require a holistic approach at various hierarchical levels (ecosystem, landscape, national and regional). While the concern of governments in managing their FGR has been increasing with the increasing introduction of relevant national policies and guidelines, there is a need for better collaboration at regional level despite the efforts already expanded by international and regional organizations. The FAO Panel of Experts on FGR has played a major role in providing recommendations at the global level and has stressed the need to strengthen national programmes and regionalcollaboration on FGR in different parts of the world. Several countries in the Asia Pacific region have taken steps to implement sustainable forest management in practice and there is a need to promote management of FGR within this process. Better management of forest genetic diversity will also help countries to fulfil their commitments as agreed under the Convention on Biological Diversity and to maintain diversity for future use. The International Plant Genetic Resources Institute (IPGRI) in collaboration with the Asia Pacific Association of Forestry Research Institutions (APAFRI) have taken the initiative to develop a regional network programme to strengthen the work on conservation and sustainable use of FGR in the region. This regional programme, called the Asia Pacific Forest Genetic Resources Programme (APFORGEN) has the support of fourteen countries in the region. The Inception workshop, organized with the technical cooperation of FAO has laid the foundation for initiating FGR networking in the region via APFORGEN. The participation of twelve country representatives in the inception workshop is an indication of support of national governments, which desire closer collaboration in FGR conservation and management.